Sum of the reciprocals of the binomial coefficients (Q685302): Difference between revisions
From MaRDI portal
Set OpenAlex properties. |
Normalize DOI. |
||
(One intermediate revision by one other user not shown) | |||
Property / DOI | |||
Property / DOI: 10.1006/eujc.1993.1038 / rank | |||
Property / DOI | |||
Property / DOI: 10.1006/EUJC.1993.1038 / rank | |||
Normal rank |
Latest revision as of 00:46, 10 December 2024
scientific article
Language | Label | Description | Also known as |
---|---|---|---|
English | Sum of the reciprocals of the binomial coefficients |
scientific article |
Statements
Sum of the reciprocals of the binomial coefficients (English)
0 references
17 October 1993
0 references
Let \(S_ n=\sum^ n_{k=0}{1 \over {n \choose k}}\). It is shown that \(S_ n\) satisfies the recurrence \(S_ n={n+1 \over 2n}S_{n-1}+1\). The proof can be simplified by observing that \[ n!S_ n=\sum^ n_{k=0}k!(n-k)!=n!+\sum^{n-1}_{k=0}k!(n-k-1)!(n+1-k-1) =n!+(n+ 1)(n-1)!S_{n-1}-(n!S_ n-n!). \]
0 references
reciprocals
0 references
binomial coefficients
0 references